An update on promising therapies for CNS conditions. (12th May 2019) - Reis, Cesar; Chen, Sheng; Tang, Jiping
ABSTRACT: In this special edition, we present five articles that explore various neurovascular and neurodegenerative diseases and update the readers on promising therapies. We discuss where the current focus of research on central nervous conditions is heading. The topics range from discussing different brain injury models simulate human physiology, to analyzing outcomes following subdural hematoma evacuation. In addition, this special issue discusses new therapeutic targets during the acute phase of brain injury. The ideas and expert analysis regarding different neurological topics set up readers to explore future research on the subject matter.